Selecting Pigs for Youth Swine Shows - Nicholas Myers; Timothy T. Marshall; William R. Walker; David L. Prichard; Bill Heltemes; Chris Decubellis; Brian Estevez; Saundra H. TenBroeck; Chad Carr (EDIS, 2012)
Are you interested in participating in a swine show? This revised 8-page fact sheet will help youth exhibitors determine how and where to purchase a project pig and provide information on what the student should look for when purchasing the pig in order to do well. Published by the UF Department of 4-H Youth Development, April 2012.